Multimedia unplugged: a workshop on learning designs at the neoMuseum, Japan - Ueda, Nobuyuki (The Turkish Journal of Pediatrics, 1999)
In Japan, we have a growing field called ’Information Education,’ but people are paying too much attention to computers and the internet. That’s why I am proposing unplugging the computer and thinking about the more essential aspects of learning and information design. ’Unplugged’ means that technology and multimedia need not be limited to digital forms. Pencil-and-paper and traditional ’by hand’ media also have important roles to play. In the Multimedia Unplugged workshop, participants use different forms of expression and media, including paper and styrofoam cubes, freeform construction kits and a wide variety of everyday objects, like bamboo leaves and post-it papers. Through this workshop, participants can understand that each medium has its own constraints and opportunities, and have a change to rethink the roles of multimedia from new perspectives. They can then replug and thus be able to choose appropriate media- digital or physical or both-to express their ideas.